2020
DOI: 10.1182/blood-2020-138614
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of a Multicenter Study of the First-in-Human Dual BCMA and CD19 Targeted Novel Platform Fast CAR-T Cell Therapy for Patients with Relapsed/Refractory Multiple Myeloma

Abstract: Introduction To further improve efficacy and duration of response of CAR-T therapy for Relapsed/Refractory Multiple Myeloma (R/R MM), we have designed a dual FasT CAR-T targeting both B cell maturation antigen (BCMA), a well-established MM target, and CD19, which is expressed on MM cells and their progenitors. Here we report early results from the first-in-human multicenter clinical study (NCT04236011; NCT04182581) to determine safety, pharmacokinetics (PK) and efficacy of BCMA-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…One emerging technology addressing this lengthy manufacturing issue is GraCell Bio’s propriety FasT CAR platform, in which product release can be achieved within 22–36 h using an expedited protocol to activate and transduce T cells without the need for further ex vivo expansion. A dual BCMA-CD19 CAR T therapy was developed using this platform and the first-in-human study has demonstrated an effective 93.8% ORR 105 . Such finding should be a precursor to further identification of key bottlenecks along the whole CAR T-cell manufacturing pipeline (Fig.…”
Section: Perspectivesmentioning
confidence: 99%
“…One emerging technology addressing this lengthy manufacturing issue is GraCell Bio’s propriety FasT CAR platform, in which product release can be achieved within 22–36 h using an expedited protocol to activate and transduce T cells without the need for further ex vivo expansion. A dual BCMA-CD19 CAR T therapy was developed using this platform and the first-in-human study has demonstrated an effective 93.8% ORR 105 . Such finding should be a precursor to further identification of key bottlenecks along the whole CAR T-cell manufacturing pipeline (Fig.…”
Section: Perspectivesmentioning
confidence: 99%
“…Bispecific CAR-T cells targeting BCMA and another tumor antigen are under development and preliminary data from the first-in-human study evaluating GC012F, a dual BCMA/CD19 targeted CAR-T cells with a platform enabling 24–36-h manufacturing, are very encouraging. 89 …”
Section: “Old” Generation Immunotherapiesmentioning
confidence: 99%
“…Furthermore, multi-target CAR-T cell therapies were created by mixing multiple CAR-T cells with a single CAR to target a different tumor-specific antigen such as BCMA + CD19, BCMA + GPRC5D, BCMA + TACO, and BCMA + SLAMF7 [ 159 , 161 ]. These CAR-T cells were engineered independently and co-administrated together or sequentially.…”
Section: Chimeric Antigen Receptor (Car) T Cell Therapy In MMmentioning
confidence: 99%
“…These CAR-T cells were engineered independently and co-administrated together or sequentially. Dual infusion of humanized anti-CD19 CAR-T cells (1.0 × 10 6 /kg) and anti-BCMA CAR-T cells (1.0 × 10 6 /kg) was performed in 21 patients with RRMM; 95% of patients achieved an ORR including 43% sCR, 14% CR, 24% VGPR, and 14% PR, and 81% of patients also showed MRD negativity [ 161 ]. AEs include CRS, which occurred in 90% of patients, including 86% patients with grade 1 or 2 and 5% with grade 3, hematological toxicities such as leukopenia, anemia, and thrombocytopenia or immunological toxicities such as cryoglobulinemia and B cell aphasia were experienced in 95% of patients with 86% patients experiencing > grade 3 [ 161 ] ( Table 5 ).…”
Section: Chimeric Antigen Receptor (Car) T Cell Therapy In MMmentioning
confidence: 99%